2012
DOI: 10.1007/s10661-012-3004-3
|View full text |Cite
|
Sign up to set email alerts
|

Element content of propolis collected from different areas of South Spain

Abstract: The aim of this work is to determine the content of essential and toxic elements in 25 raw propolis samples, when considering pollution agents and geographical and botanical factors. The microwave-assisted digestion was the most reliable and accurate method for determination of inorganic elements in propolis samples. The results were obtained using certified reference materials in a good agreement with certified values. Inductively coupled plasma atomic emission spectroscopy was used for the determination of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 28 publications
12
38
2
1
Order By: Relevance
“…Compared to propolis produced in South Spain (Bonvehí and Bermejo, 2013), the concentrations of Ca, Na, and Fe reported in our study were very similar and those of Mg, K, and Cu were within the reported range. However, Zn concentrations were relatively low.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Compared to propolis produced in South Spain (Bonvehí and Bermejo, 2013), the concentrations of Ca, Na, and Fe reported in our study were very similar and those of Mg, K, and Cu were within the reported range. However, Zn concentrations were relatively low.…”
Section: Discussionsupporting
confidence: 85%
“…Finger et al (2014) studied the concentrations of 11 representative metals in some regions of the Paraná state in South Brazil, and they demonstrated that the concentrations of aluminum (Al), Ca, and Mg differed in some regions, which could be used to identify not only the geographical origin of propolis, and to identification of specific zones with environmental contamination. Similar studies have been undertaken in other countries such as those by Cantarelli et al (2011) in Argentina, Gong et al (2012) in China, and Bonvehí and Bermejo (2013) in Spain.…”
Section: Introductionsupporting
confidence: 57%
“…The results obtained here are in good agreement with the data published by Formicki and Bogdanov [6,36], who point out that low level of lead (Pb min = 0.06 mg kg -1 ) was found in the propolis collected in Poland taken from the Raciechowice location. The content of lead in propolis collected in 2013 was determined by SerraBonvehi and Bermejo Oranteson [37], and their reported value of 3.80 mg kg -1 is higher compared to the value determined in our study.…”
Section: Concentrations Of Cu Pb CD Cr and Zn (Mg Kgcontrasting
confidence: 70%
“…More than 300 chemical compounds have been identified from propolis, including polyphenol (eg, flavonoids), coumarin, terpenes, amino acids, minerals, etc. [2,3,4,5,6]. This product has attracted the interest of researchers in recent decades because of the properties of biological and pharmacological, among others such as antimicrobial [7,8,9], antitumor [10], immunomodulator [11], anti-inflammatory [12], an antioxidant [13].…”
Section: Introductionmentioning
confidence: 99%